Analisis Pengaaruh Pengungkapan Environmental, Social Dan Governance (ESG) Terhadap Nilai Perusahaan Dalam Sektor Manufaktur Dan Minuman Di Bursa Efek Indonesia Tahun 2020 - 2023 - Salsabila, Firyal Hasna; Malikah, Anik; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine the effect of environmental, social and governance (ESG) disclosure on company value in companies listed on the Indonesia Stock Exchange in the 2020 - 2023 period. This study uses a type of quantitative data with a type of secondary data sourced from annual reports and sustainability reports for the 2020 - 2023 period. The sample selection method uses purposive sampling. This study uses a sample of manufacturing companies in the fields of food, beverage, pharmaceuticals and infrastructure listed on the Indonesia Stock Exchange during the period of 2020-2022. The number of companies sampled in this study is 10 companies for 4 years with a total of 40 sample data. The data analysis technique used in this study is linear regression of panel data using E-views 12 and SPSS v 22 with the best model choice being the Common Effect Model. The results of this study show that the variables of Environmental disclosure, Social disclosure, and Governance disclosure havea positive and significant effect on company value. Keywords: Environmental disclosure, Social disclosure, Governance disclosure, company value.